The impact of the COVID-19 pandemic on transcatheter aortic valve implantation (TAVI) service: a United Kingdom tertiary centre experience. (14th October 2021) - Tan, J H; Teoh, T K; Ivanova, J; Jadhav, S; Varcoe, R; Baig, K; Gunarathne, A
Abstract: Background/Introduction: Untreated, symptomatic, severe aortic stenosis carries significant mortality and morbidity. Timely intervention is pivotal to ensure patient safety. The COVID-19 pandemic created unprecedented challenges to the UK's National Health Service (NHS), resulting in the deferral of all elective work, including TAVI services from March 2020. Purpose: To evaluate clinical outcomes and time delays in patients undergoing TAVI during the pandemic period compared to an age and risk factor-matched cohort of patients prior to COVID-19. We hypothesized that there were significant time delays, more emergency procedures and related adverse outcomes in patients who underwent TAVI during the pandemic period. Methods: We analysed prospectively collected data (patient characteristics, procedural details, complications and in-hospital outcomes) of 210 consecutive patients who underwent TAVI between March 2019 and February 2021 in a tertiary centre in the UK (The centre serves for a population of 2.5 million and provided in-patient treatment for 5590 COVID-positive patients over a 12 month period). We compared time-lags from an initial referral to outpatient review, CT aortograms, valve implantation and 30-day mortality between patients who underwent TAVI between March 2019 and Feburary 2020 (N=134) and those who underwent TAVI between March 2020 and February 2021 (COVID Group=76). Results: The mean age of the cohort was 81.4±6.6 years and majority were females (51%) and were in moderate risk category (EuroSCORE II=4.55±5.5). Of the total cohort, 4 (5.3%) patients acquired COVID-19 pneumonia during the hospital stay. The age, cardiovascular comorbidities and risk scores were comparable between the control group and the COVID cohort. (Table 1). There were no significant differences in procedural complications in the control group compared to the COVID-19 group (Table 1). The median waiting time from referral to TAVI clinic was significantly shorter in the COVID-19 group (33 (8–66) vs. 51 (17–89) days (P=0.04)) and there was no significant difference in time delays for CT aortogram, MDT or TAVI procedure between the two groups. The median length of stay (2 (2–4) vs 2.5 (2–9) days) and 30 day mortality (1.4% vs 5.3%) was comparable between the two groups (Table 1). Conclusion: Contrary to our hypothesis, our analysis demonstrated that there were no significant time delays, excess complications or mortality in TAVI procedures during the COVID-19 pandemic period despite the excess burden imposed on our local health services. More importantly, very few TAVI patients acquired COVID-19 infection during in-hospital stay. This is likely due to prompt identification of innovative ways of re-configuring an existing local patient pathway, by the TAVI team, to deliver safe and uninterrupted TAVI services during this unprecedented pandemic setting. Funding Acknowledgement: Type of funding sources: None.